2015
DOI: 10.1007/s00436-015-4434-y
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum in wild rodents: reservoirs or just irrelevant incidental hosts?

Abstract: Wild rodents constitute a very large biomass of potential reservoirs for Leishmania spp. Therefore, an epidemiological study was carried out in a well-known focus of canine leishmaniasis from southern Spain, with the objective of detecting and characterizing Leishmania infantum infection in wild rodents. Blood, liver, spleen, bone marrow, and skin from 37 rodents (24 Apodemus sylvaticus, 9 Rattus rattus, and 4 Mus musculus) were analyzed by optical microscopy, culture, and two different polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 44 publications
3
38
0
2
Order By: Relevance
“…These animals had confirmed Leishmania infection in endemic areas for human leishmaniasis in Ethiopia (Kassahun et al 2015) and for canine leishmaniasis in Spain (Navea-Pérez et al 2015), by molecular techniques. Also in Brazil, infection by L. (L.) infantum was detected by PCR in spleen and skin samples of wild rodents coming from rural areas (Lima et al 2013).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These animals had confirmed Leishmania infection in endemic areas for human leishmaniasis in Ethiopia (Kassahun et al 2015) and for canine leishmaniasis in Spain (Navea-Pérez et al 2015), by molecular techniques. Also in Brazil, infection by L. (L.) infantum was detected by PCR in spleen and skin samples of wild rodents coming from rural areas (Lima et al 2013).…”
Section: Discussionmentioning
confidence: 92%
“…These three species belong to the Order Carnivora, which also includes L. vetulus and C. thous, two species that are known natural reservoirs of the parasite. It seems important to investigate the exact role of wild species that have been reported with L. (L.) infantum infections, including those described in the present study, since it is clear that the classic cycle of VL, dog-sandflyhuman, is probably much more complex than previously thought and may involve a network of animal species (Navea-Pérez et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Our prevalence based on ELISA was higher (23.3%) than previously reported (0% in Brazil and 4.1% in Sudan) and based on IFAT was lower (3.3%) than that of previous reports (27.2% in Tunisia and 51.3% in Brazil). The PCR prevalence was nine of 127 animals (7.1%), which is a low prevalence upon comparing to other studies performed in Brazil (BRANDÃO-FILHO et al, 2003;OLIVEIRA et al, 2005;QUARESMA et al, 2011;LIMA et al, 2013;CARDOSO et al, 2015;FERREIRA et al, 2015), South America (ALEXANDER et al, 1998;LIMA et al, 2002), Iran (AKHAVAN et al, 2010;DAVAMI et al, 2013;MIRZAEI et al, 2014), Saudi Arabia (IBRAHIM et al, 1992), Italy (ZANET et al, 2014), Spain (NAVEA-PÉREZ et al, 2015), and Portugal (HELHAZAR et al, 2013). This low prevalence in PCR could be explained by our use of total blood as sample; most other studies used both blood and tissue (liver, spleen, skin, bone marrow).…”
Section: Discussionmentioning
confidence: 97%
“…R. rattus has previously been found to be naturally infected and L. (V.) braziliensis in several places around the world such as Brazil (ALENCAR et al, 1960;BRANDÃO-FILHO et al, 2003;SVOBODOVÁ et al, 2003;OLIVEIRA et al, 2005;QUARESMA et al, 2011;LIMA et al, 2013) and other countries (LIMA et al, 2002;ZULUETA et al, 1999;DAVAMI et al, 2013;EL ADHAMI, 1976;IBRAHIM et al, 1992;POZIO et al, 1981;DI BELLA et al, 2003;ZANET et al, 2014;NAVEA-PÉREZ et al, 2015;VLADIMIR et al, 2015 andSINGH et al, 2013). As in this work, other studies have found rats captured in the same place with more than one Leishmania species: Lima et al (2002) found L. (SILVEIRA et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the species mentioned above, rodents are of particular interest regarding L. infantum transmission in Europe, where the black rat ( Rattus rattus), the Norwegian rat ( Rattus norvegicus), house mouse ( Mus musculus ), wood mouse ( Apodemus sylvaticus ) and the Algerian mouse ( Mus spretus ) have been found to be infected . These animals exist in enormous populations and are considered possible reservoirs of the parasite , but their role in the epidemiology of leishmaniosis is still largely unknown and needs to be further investigated and elucidated .…”
Section: Introductionmentioning
confidence: 99%